The first dynasty of Islam : the Umayyad Caliphate AD 661-750 - Hawting, G. R. (Gerald R.), 1944- (Routledge, 2000)
The standard work on this complex period in Arab history is available once again with the addition of a new introduction by the author which examines recent significant contributions to scholarship in the field.